2011
DOI: 10.1055/s-0031-1280128
|View full text |Cite
|
Sign up to set email alerts
|

FlavoneC-glycosides from the Leaves ofLophatherum gracileand TheirIn VitroAntiviral Activity

Abstract: Four new flavone C-glycosides, luteolin 6-C-α-L-arabinopyranosyl-7-O-β-D-glucopyranoside, apigenin 6-C-β-D-galactopyranosiduronic acid (1 → 2)-α-L-arabinopyranoside, luteolin 6-C-β-D-galactopyranosiduronic acid (1 → 2)-α-L-arabinopyranoside, and luteolin 6-C-β-D-glucopyranosiduronic acid (1 → 2)-α-L-arabinofuranoside, along with three known ones, were isolated from the leaves of Lophatherum gracile. The structures of the new compounds were elucidated by extensive spectroscopic methods as well as acid hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…The 13 C NMR and DEPT spectra of compound 1 displayed 27 carbon signals due to one flavone aglycone and two sugar moieties. The proton and carbon signals corresponding to the aglycone part of compound 1 were in good agreement with those of luteolin (4,5). The two sugar units in compound 1 were identified as b-D-galactopyrano-siduronic acid and b-D-glucopyranose, respectively, by comparison with the NMR data with those reported in the literatures (5,13).…”
Section: Identification Of the Isolated Compoundssupporting
confidence: 79%
See 3 more Smart Citations
“…The 13 C NMR and DEPT spectra of compound 1 displayed 27 carbon signals due to one flavone aglycone and two sugar moieties. The proton and carbon signals corresponding to the aglycone part of compound 1 were in good agreement with those of luteolin (4,5). The two sugar units in compound 1 were identified as b-D-galactopyrano-siduronic acid and b-D-glucopyranose, respectively, by comparison with the NMR data with those reported in the literatures (5,13).…”
Section: Identification Of the Isolated Compoundssupporting
confidence: 79%
“…The proton and carbon signals corresponding to the aglycone part of compound 1 were in good agreement with those of luteolin (4,5). The two sugar units in compound 1 were identified as b-D-galactopyrano-siduronic acid and b-D-glucopyranose, respectively, by comparison with the NMR data with those reported in the literatures (5,13). In the ROESY spectrum of compound 1, correlation between H-1 000 (d H 4.16) of the galacturonic acid and H-1 00 (d H 4.64) of the glucose indicated that the galacturonic acid was attached to the C-2 00 of glucose.…”
Section: Identification Of the Isolated Compoundssupporting
confidence: 79%
See 2 more Smart Citations
“…Polysaccharides purified from LH possess strong anti-oxidant capabilities28, and oral administration of LH flavonoids exerts a protective effect on restraint stress-induced liver injury in mice29. In addition, flavone C-glycosides isolated from LH show potent anti-viral activity against human respiratory syncytial virus (RSV)30.…”
mentioning
confidence: 99%